Evolution of Hindu Administrative Institutions in South India - Aiyangar, S. Krishnaswami, (Brill | Manohar Publishers & Distributors, 2024)
Aiyangar's celebrated work Evolution of Hindu Administrative Institutions in South India examines the administration and political frameworks adopted by different South Indian kingdoms. It also discusses about differences between South Indian and North Indian polity. The author also covers the political ideology of ancient South Indian states, such as kural system and other features in this volume. Lastly, this book covers the administrative policy under Pallavas and Cholas, and rural politics under the Cholas.